Expected Progeny Differences (EPDs) in Beef Cattle - Gary R. Hansen; David G. Riley (EDIS)
AN164, a 14-page fact sheet by Gary R. Hansen and David G. Riley, describes how to use Expected Progeny Differences (EPDs) to evaluate prospective breeding stock. Includes 6 pages of tables. Published by the UF Department of Animal Sciences, April 2006.